2019
DOI: 10.1039/c9sc03532j
|View full text |Cite
|
Sign up to set email alerts
|

Metallohelices that kill Gram-negative pathogens using intracellular antimicrobial peptide pathways

Abstract: Iron-based self-assembled optically pure compounds mimic the mechanisms of small peptides, according to biophysical, genomic, transcriptomic and other analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 84 publications
(99 reference statements)
3
37
0
Order By: Relevance
“…A similar structure binds to the central hydrophobic α‐helical region of an amyloid β protein and attenuates toxicity . Perhaps most convincingly, we showed recently that a class of antimicrobial metallohelix in our library rapidly penetrates the formidable cell envelope of a clinically‐relevant Gram negative microbe and causes a peptide‐like genomic and transcriptomic response.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…A similar structure binds to the central hydrophobic α‐helical region of an amyloid β protein and attenuates toxicity . Perhaps most convincingly, we showed recently that a class of antimicrobial metallohelix in our library rapidly penetrates the formidable cell envelope of a clinically‐relevant Gram negative microbe and causes a peptide‐like genomic and transcriptomic response.…”
Section: Introductionmentioning
confidence: 68%
“…Our recent success in CuAAC derivatization of metallohelices using relatively simple functionality, and an in cellulo click staining protocol, gave us confidence to attempt the rather more ambitious glycoconjugations. We report here that this chemistry, giving rise to some of the most complex functionalized metallosupramolecular structures known, proceeds smoothly and efficiently, leading to improved cancer‐cell targeting in vitro, and improved efficacy in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a very recent report on helicates, published as we compiled this study, showed that bacterial resistance to such systems also involves reduction of net negative surface charge. 84 Cell walls densely functionalized with the glycopolymers teichoic acid and lipoteichoic acids also provides an additional barrier to uptake toward 4 4+ .…”
Section: Discussionmentioning
confidence: 99%
“…We recently studied the interaction of 5b – h with various DNA G-quadruplexes including human telomeric G-quadruplex and our results revealed that some of the metallohelices prefer binding to G-quadruplexes over double-helical DNA (Ref. 36 and unpublished data). The results suggest that the high binding affinity of 5b to DNA G-quadruplexes might contribute to its biological activity.…”
Section: Introductionmentioning
confidence: 87%
“…Metallohelix 5a was shown to exhibit promising antimicrobial activity 35 and served as a prototype compound for the development of a new class of metallohelices 5b – h (Fig. 1 A) with structure-dependent activity against Gram-positive and -negative bacteria 36 . Additionally, we showed recently 37 that for instance, metallohelices 5b and 5f accumulate in eukaryotic cells and that a significant fraction of the metallohelices accumulates in the cell nucleus allowing them to interact also with nuclear nucleic acids.…”
Section: Introductionmentioning
confidence: 99%